Acute cardiopulmonary responses to strength training, high-intensity interval training and moderate-intensity continuous training - Falz, R.; Fikenzer, S.; Holzer, R.; Laufs, U.; Fikenzer, K.; Busse, M. (European Journal of Applied Physiology, 2019)
Purpose: Long-term effects of exercise training are well studied. Acute hemodynamic responses to various training modalities, in particularly strength training (ST), have only been described in a few studies. This study examines the acute responses to ST, high-intensity interval training (HIIT) and moderate-intensity continuous training (MCT). Methods: Twelve young male subjects (age 23.4 ± 2.6 years; BMI 23.7 ± 1.5 kg/m2) performed an incremental exertion test and were randomized into HIIT (4 × 4-min intervals), MCT (continuous cycling) and ST (five body-weight exercises) which were matched for training duration. The cardiopulmonary (impedance cardiography, ergo-spirometry) and metabolic response were monitored. Results: Similar peak blood lactate responses were observed after HIIT and ST (8.5 ± 2.6 and 8.1 ± 1.2 mmol/l, respectively; p = 0.83). The training impact time was 90.7 ± 8.5% for HIIT and 68.2 ± 8.5% for MCT (p < 0.0001). The mean cardiac output was significantly higher for HIIT compared to that of MCT and ST (23.2 ± 4.1 vs. 20.9 ± 2.9 vs. 12.9 ± 2.9 l/min, respectively; p < 0.0001). VO2max was twofold higher during HIIT compared to that observed during ST (2529 ± 310 vs. 1290 ± 156 ml; p = 0.0004). Among the components of ST, squats compared with push-ups resulted in different heart rate (111 ± 13.5 vs. 125 ± 15.7 bpm, respectively; p < 0.05) and stroke volume (125 ± 23.3 vs. 104 ± 19.8 ml, respectively; p < 0.05). Conclusions: Despite an equal training duration and a similar acute metabolic response, large differences with regard to the training impact time and the cardiopulmonary response give evident. HIIT and MCT, but less ST, induced a sufficient cardiopulmonary response, which is important for the preventive effects of training; however, large differences in intensity were apparent for ST.